Experimental Realization of Parrondo's Paradox in 1D Quantum Walks. Issue 6 (10th May 2020) - Jan, Munsif; Wang, Qin‐Qin; Xu, Xiao‐Ye; Pan, Wei‐Wei; Chen, Zhe; Han, Yong‐Jian; Li, Chuan‐Feng; Guo, Guang‐Can; Abbott, Derek
Abstract: The Parrondo effect is a well‐known apparent paradox where a combination of biased random walks displays a counterintuitive reversal in direction. These random walks can be expressed in terms of classical coin tossing games, leading to the surprising result that a combination of losing games can result in a winning game. There is now a large body of literature on quantum walks theoretically analyzing the quantum version of this effect, but to date, there have been no experimental observations of quantum Parrondo walks. Here, the first experimental verification of a quantum Parrondo walk within a quantum optics scenario is demonstrated. Based on the compact large‐scale experimental quantum‐walk platform, two rotation operators are implemented to realize the quantum Parrondo effect. The effect of quantum coherence in a quantum Parrondo walk is also investigated based on a delayed‐choice scheme that cannot be realized with classical light. It is demonstrated that the Parrondo effect vanishes when the quantum walk has a completely decoherent initial state in a delayed‐choice setting. Quantum walks are fundamental to multiple quantum algorithms, and this research provides motivation to expand the results to further explore quantum Parrondo walks. Abstract : Parrondo's paradox describes a counterintuitive result of combining two individually losing games to produce a winning outcome. Assisted by the coherent character of the quantum system, an experimental study of the quantum Parrondo walk, that is, how two biased walks can be correlated to cause a counterintuitive reversal in direction, is realized with photonic quantum crystals.